What does testosterone do for red deer males? - Malo, A; Roldan, E; Garde, J; Soler, A; Vicente, J; Gortazar, C; Gomendio, M (2009)
Testosterone has been proposed to have a dual effect, enhancing sexual traits while depressing parasite resistance in males. Here, we test this hypothesis in red deer, examining males from captive populations during the whole annual cycle and males from natural populations during the breeding season. We first explored the effects of body size, age and sampling date on testosterone to avoid confounding effects. Our results show that in captive populations seasonal changes in testosterone levels were mirrored by changes in testes size, and that during the rut there was a strong correlation between both. In natural populations, males with higher testosterone levels had larger testes, improved sperm quality, smaller burr diameter, stronger antlers, higher haematocrit levels, and increased nematode parasite load. By contrast, no significant relationship was found between testosterone and spleen size or tick parasite load. We conclude that testosterone (i) improves males' reproductive investment and physical stamina, (ii) improves antler strength but reduces burr diameter, and (iii) imposes a cost in terms of depressed parasite resistance.